(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: The administration of antibiotics is of great value in the therapy of infections of male genital tract, which may have an effect on fertility. Antibiotics are generally prescribed for a variety of infections. A number of patients requiring assisted conception occasionally show evidence of reproductive tract infections. While fluoroquinolones being excessively prescribed in the treatment of male genital tract infections, too little information concerning their outcome on fertility are present. Objective: To estimate ciprofloxacin effects on sperm function parameters in addition to inspect whether ciprofloxacin can affect the integrity of sperm DNA. Methods: In the present study, 48 male adult rats were enrolled. The animals were randomly allocated into six groups; four ciprofloxacin treated groups, which were treated with either (40 mg/kg/day) or (80 mg/kg/day) of ciprofloxacin and 2 control groups. For each dose, the treatment maintained for either 14 days or 28 days. At the end of each duration of treatment, certain epididymal sperm function parameters: sperm morphological normality, sperm concentration and sperm motility were analyzed together with sperm DNA integrity analysis. Results: A significant reduction in sperm concentration, motility and percentage of morphologically normal sperm (in a dose dependent manner) was observed when ciprofloxacin administered for 28 days. The level of DNA fragmentation was significantly elevated with a significant reduction in sperm chromatin quality in ciprofloxacin treated groups whereas serum testosterone level was not significantly affected. Conclusion: Ciprofloxacin can adversely influence fertility parameters in male rat. Keywords: Fertility, Ciprofloxacin, Sperm DNA Citation: Abd AH, Al-Dujaily SS, Al-Saray DA. Effects of ciprofloxacin on male fertility parameters and sperm DNA integrity in rats. Iraqi JMS. 2018; 16(4): 378-384. doi: 10.22578/IJMS.16.4.4